Victim-blaming and image-based sexual abuse - Flynn, Asher (Journal of criminology, 2023)
Image-based sexual abuse (IBSA) is a growing, global problem. This article reports on a mixed-methods, multi-jurisdictional study of IBSA across the United Kingdom, Australia and Aotearoa/New Zealand. Attitudes of blame and minimisation of harms among a sample of the general population (n?=?6109) were analysed using two multiple regression analyses that assessed the ability of three demographic and three experiential characteristics to predict attitudes. Interviews were also conducted with 43 stakeholders and analysed thematically. Survey respondents who attributed more blame and minimised harms to a greater extent tended to be men, heterosexual, and had experienced or perpetrated more IBSA behaviours. Those who reported greater engagement in sexual self-image behaviours were also more likely to minimise harms. Interview participants suggested attitudes of blame and minimisation may be linked to broader problematic attitudes around sexual violence and sexual double standards, with women more likely to experience blame for IBSA. Our findings are of international relevance and highlight the need for multifaceted policies, education campaigns and training that challenge these attitudes.